Modal Sosial dan Perilaku Pro-Lingkungan pada Wisata Pesisir Pohuwato: Literature Review - Sitti Mutiah Rahman; Wawan K. Tolinggi; Irwan Bempah (Transbahasa, 2026)
Coastal tourism in Pohuwato Regency has significant potential to support community economic development, while also requiring environmental management that involves active community participation. This article aims to examine the role of social capital in encouraging pro-environmental behavior in coastal tourism areas, particularly at Pohon Cinta Beach. The study employed an integrative literature review method. A thematic search across Google Scholar, the SINTA portal, and Garuda for the 2021–2026 period yielded around 60 records, which were screened and reduced to 22 peer-reviewed national and international journal articles, supplemented by several seminal theoretical sources on social capital, environmental sociology, and coastal tourism governance. The results indicate that trust plays a role in strengthening collective action and supporting the acceptance of community-based environmental programs. Social norms derived from local wisdom and religious values ​​also shape informal environmental control mechanisms. In addition, social networks involving Pokdarwis (tourism groups), village institutions, NGOs, and universities contribute to expanding community access to knowledge, cooperation, and resources to support environmental management. The reviewed literature also indicates several aspects that need to be strengthened, such as increasing environmental literacy, strengthening inter-institutional coordination, optimizing funding support, and developing more integrated management mechanisms. Therefore, strengthening social capital through the utilization of local wisdom, developing institutional collaboration, and increasing community environmental literacy are important parts in supporting sustainable coastal tourism management in Pohuwato Regency.